SERVICE ORIENTED ENTERPRISES - Setrag Khoshafian (AUERBACH PUBLICATIONS, 2007)
Ideas achieve their potential only if the context is appropriately understood. Without proper context even great ideas are underserved, markets are missed, and leaders of industry fall. This book provides a novel case for the business context in which to apply the important technical idea of service orientation and moves it from being an interesting tool for engineers to a vehicle for business managers to fundamentally improve their businesses. This is a critical time for such an idea to be properly applied. An accelerating competitive drum demands that businesses change at a pace that was inconceivable a decade ago. Business must respond with ever faster continuous improvement of existing operations and the constant introduction of new products, and only companies that master the required rhythm of change will persevere and prosper. Businesses that learn to build in a capacity for rapid change are becoming the fiercest and boldest competitors. Service orientation starts as a powerful technical idea to operationalize the goal of rapid enterprise change by allowing business processes to negotiate diverse systems. This offers a technical advantage as it becomes easier to integrate systems and to reposition existing capabilities for new purposes. Silos of technology that were hidden in arcane interfaces become reusable components that are accessible through transparent standards. But an organization that only adopts service orientation as a technical architecture is missing the true potential of the concept. The service orientation revolution will fully empower organizations that apply it to both their technology and their culture. The proper context for service orientation extends beyond the technical architecture to the very philosophy of how a business should operate.